Retail Store Merchandise Assortment and Display and their Influence on Consumer Impulse Buying Behaviour in North-west Nigeria. (Global Journal of Management and Business Research, 2015)
This paper determined the influence of retail store merchandise assortment and display on consumer impulse buying behavior in north-west Nigeria. Two specific purposes were set with two research questions to guide the study. Two null hypotheses were formulated for the study and were tested at .05 level of significance. The study was conducted in 10 Colleges of Education in North-west Nigeria on a target population of Business Education Lecturers. A total of 219 Lecturers who teach Business Education courses in the colleges and who also patronize retail stores as consumers were studied. A structured questionnaire called "Influence of Retail Store Merchandise Assortment and Display on Consumer Impulse Buying Behaviour (IRSMADCIBB)" was used to obtain data for the study. The instrument was structured on a fivepoint Likert scale.
Keywords: merchandise assortment; merchandise display; impulse buying; consumer behaviour